Prediction of Moisture Content Removal from Sludge by Artificial Neural Network Modelling - Zhi Fu, Joidan Lau (Universiti Teknologi PETRONAS, 2020)
This study predicted the moisture content removed from sludge samples which underwent oven-dry tests by means of neural artificial network modelling. Sludge management is a global predicament in which challenges in solving it include cost- saving, space usage-optimization, and environmentalism. Information pertaining to drying sludge and removing its moisture content is pertinent as it determines sludge management quality as it determines the costs of management. Hence, a model predicting sludge moisture content could help provide more insight into dewatering sludge which is often overlooked, in contrast to techniques of dewatering sludge. There remains a dearth of research done in this regard. Hence this endeavor is worthwhile for the potential expansions of such work may make headway to more profitable discoveries.